Tackling COVID-19 in informal tented settlements (Lebanon): An assessment of preparedness and response plans and their impact on the health vulnerabilities of Syrian refugees - Paul Moawad; Lauren Andres (Elsevier, 2020)
Abstracts: This paper is exploring and critically accessing the nature and mechanisms of preparedness and response plans to COVID-19 in Syrian ITSs in Lebanon along with their immediate health impacts on refugees and their abilities to survive. Little is known to date about how such plans have been set up and how they have immediately impacted refugees, particularly those in countries affected by severe economic and political turbulences along with fragile health systems. This qualitative study has been conducted during the pandemic and hence is providing important and novel insights into a time-limited research window during which not only refugees' mobility was restricted but also research capabilities severely constrained. We are focusing on the relationships between refugees, health and the COVID-19 pandemic and unwrapping how very strict and control-led preventive mechanisms have emerged as a consequence of already stretched and problematic health and socio-economic systems. We are also demonstrating how the multi-level strategy and local responses have led to significant challenges to local municipalities, local NGOs and international aid agencies in order to reduce transmission risks in very unhealthy settings as they try to address wider needs. This paper concludes that the impact of the constraining preventive measures implemented to date means that refugee communities will suffer consequences for months and years to come, with their ability to survive being threatened and an expected long-term health impact for a population already at high risk of NCDs. We argue that more research will be needed into deconstructing further refugees' reactions to encampment mechanisms and mobility restrictions, particularly if survival becomes even more problematic; similarly relationships and tensions with local municipalities, as well as measures and support provided by local and international NGOs, will deserve attention. A key question remains about the likely scenario if cases start to spread widely in ITSs and, hence, what will happen to both refugees and host communities in a country with a health system on the edge of collapse.